Cell apoptosis specific marker found by Fourier Transform Infrared Spectroscopy. Issue 3 (2004) - Gaudenzi Gaudenzi, Silvia Silvia; Pozzi Pozzi, Deleana Deleana; Toro Toro, Paolo Paolo; Silvestri Silvestri, Ida Ida; Morrone Morrone, Stefania Stefania; Castellano Castellano, Agostina Congiu Agostina Congiu
Abstract : We used Fourier Transform Infrared Spectroscopy (FTIR) combined with flow cytometry to study the apoptosis and necrosis processes in Jurkat, a lymphocyte cell line. The apoptosis was induced in the cells by a chemical agent, the actinomycin D, while the necrosis was induced lowering the pH value to 4.2. The apoptotic events were analysed by flow cytometry (using annexin V and propidium iodide) and contemporary monitored by FTIR spectroscopy at different times after the treatment. This comparison allowed us to find in the IR spectrum, between 3000 cm −1 and 2800 cm −1, a "marker band" of the apoptosis corresponding to the exposure of phosphatidylserine on the outer leaflet of the membrane. A marker of a specific cellular process obtained by using a non‒destructive technique such as FTIR spectroscopy, has a great significance in the diagnostic medicine providing a tool for detecting pathologies in vivo .